Composition, structure and function of the Helicobacter pylori cag pathogenicity island encoded type IV secretion system - Backert, Steffen; Tegtmeyer, Nicole; Fischer, Wolfgang (Future Microbiology, 2015)
Many Gram-negative pathogens harbor type IV secretion systems (T4SS) that translocate bacterial virulence factors into host cells to hijack cellular processes. The pathology of the gastric pathogen Helicobacter pylori strongly depends on a T4SS encoded by the cag pathogenicity island. This T4SS forms a needle-like pilus, and its assembly is accomplished by multiple protein-protein interactions and various pilus-associated factors that bind to integrins followed by delivery of the CagA oncoprotein into gastric epithelial cells. Recent studies revealed the crystal structures of six T4SS proteins and pilus formation is modulated by iron and zinc availability. All these T4SS interactions are crucial for deregulating host signaling events and disease progression. New developments in T4SS functions and their importance for pathogenesis are discussed.
Created from Fastlane, Scopus look-up
Keywords: c-Met; CagA; CagL; cagPAI; CagY; cortactin; EGF receptor; gastric disease; GTPase; Helicobacter pylori; integrin; MARK2/PAR1b kinase; signaling; T4SS; type IV secretion; tyrosine kinases; VirB proteins; β-catenin